PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP MOTIVASI KERJA GURU - supardi supardi (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The purpose of the study was to know (1) the ability of the leadership of Principal in increase the motivation of teachers, (2) the job motivation of teachers in carrying out their duties in accordance with the position and function, (3) Factors that become barriers for principal in increasing job motivation of teachers. The data source of the study was all of the teachers and education personnel on the state elementary school of Mangkujajar in 2016 which amounted to 10 people. The study used the description facultative with the instruments used are the result of performance of teachers and education personnel in the form of SKP or DP3 of the principal and the results stuffing covered respondents and interviews. Analysis of the data used was the qualitative and quantitative analysis using a statistical correlation. The results showed that there was a significant relationship between the leadership of the Principal with teachers’ work motivation.